The influence of effort expectancy, performance expectancy, and social influence on perceived risk, behavioral intention, and actual use moderated by user trust in social commerce in Indonesia - Hendrajaya, Cuk Taruna; Brahmasari, Ida Aju; Ratih, Ida Aju Brahma (Edelweiss Applied Science and Technology, 2024)
This research aims to investigate the effects of performance expectancy, effort expectancy, and social influence on perceived risk, behavioral intention, and actual use; the effect of perceived risk on behavioral intention and actual use; and the effect of behavioral intention on actual use, as well as the moderating role of trust in the relationship between perceived risk and actual use. The population for this study is not limited, thus a sampling method is required. The sampling method used in this study is purposive sampling. The criteria for determining the sample in this study are respondents aged 18 and above, as it is expected that respondents can understand the questions in the questionnaire and provide valid answers, and consumers who have made online purchases in social commerce in the last month. A total of 270 respondents were obtained after distributing the questionnaire, which were then analyzed using SEM analysis with the help of AMOS 22. The results show that performance expectancy has a significant effect on perceived risk, performance expectancy has a significant effect on behavioral intention, performance expectancy has no significant effect on actual use, effort expectancy has no significant effect on perceived risk, effort expectancy has a significant effect on behavioral intention, effort expectancy has no significant effect on actual use, social influence has no significant effect on perceived risk, social influence has no significant effect on behavioral intention, social influence has no significant effect on actual use, perceived risk has no significant effect on behavioral intention, perceived risk has no significant effect on actual use, behavioral intention has a significant effect on actual use, and trust significantly moderates the effect of perceived risk on actual use.